Atrial flutter and nonconducted bigeminy premature atrial contraction in a neonate with cardiac rhabdomyoma - Yakup Ergül; Erkut Öztürk; Alper Güzeltaş (KARE Publishing, 2018)
During the neonatal period the majority of cardiac tumors seen are rhabdomyomas, and the clinical manifestations are notably variable. Symptoms of rhabdomyoma depend on the presence of intracardiac obstructions, myocardial involvement, or rhythm disturbances. Most cardiac rhabdomyomas regress in follow-up, but some need medical/surgical intervention during the neonatal period as a result of resistant atrial or ventricular arrhythmia. The present case study is a description of an 8-day-old neonate with atrial bigeminy that caused nonconducted premature pulse-related bradycardia, and cardiac rhabdomyoma-related resistant atrial flutter that were detected and successfully treated.